2020
DOI: 10.21203/rs.3.rs-52216/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A key role of gut microbiota-vagus nerve axis and gut microbiota-spleen axis in sleep deprivation-mediated aggravation of systemic inflammation after LPS administration

Abstract: Background: Sleep deprivation (SD) is shown to be correlated with exacerbated systemic inflammation after sepsis. However, the underlying mechanisms remain unclear. Methods: In this study, mice were intraperitoneally injected with lipopolysaccharide (LPS) followed by 3 consecutive days of SD. The subdiaphragmatic vagotomy (SDV) was performed 2 weeks before LPS injection. The pseudo germ-free mouse model was created by administering antibiotics for 14 consecutive days, and then fecal microbiota transplant (FMT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Above all, we want to explore the effects of REM sleep deprivation on anesthetic potency as the determination of LORR ED 50 required a period of 0.5-1 h though it is not too long, we do not know that if the sleep debt can be discharged during anesthesia, whereas as mentioned above, inhaled anesthetics cannot satisfy the homeostatic need for REM sleep, so we can exclude the effect of anesthetic time on our results. Also, modified multiple platform method was widely used for REM sleep deprivation [4,30,31] and it is convenient to model.…”
Section: Selection Of Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Above all, we want to explore the effects of REM sleep deprivation on anesthetic potency as the determination of LORR ED 50 required a period of 0.5-1 h though it is not too long, we do not know that if the sleep debt can be discharged during anesthesia, whereas as mentioned above, inhaled anesthetics cannot satisfy the homeostatic need for REM sleep, so we can exclude the effect of anesthetic time on our results. Also, modified multiple platform method was widely used for REM sleep deprivation [4,30,31] and it is convenient to model.…”
Section: Selection Of Methodsmentioning
confidence: 99%
“…Sleep deprivation in mice was achieved by modified multiple platform method [4]. The mice were placed on 9 circular and 3.5 cm-diameter platforms in a ventilated transparent cage (50 × 30 × 17 cm, available food and water, 4 mice/cage) filled by water up to 1 cm of the platforms' surface enabling the mice to jump between the platforms.…”
Section: Sleep Deprivationmentioning
confidence: 99%
“…The gut microbiota produces obesity by affecting the host diet and metabolism. The intestinal flora was found to increase host appetite by reducing G protein-coupled receptor 5 activation and 44 serotonin (Zhang H, Butoyi C, Yuan GY, et al, 2023). In addition, Cani found that the intestinal microflora can participate in the regulation of adipose tissue metabolism through the LPS-eCB regulation ring, leading to obesity and abdominal fat accumulation (Cani PD, Plovier H, Hul MV, et al, 2015).…”
Section: Disordered Intestinal Microfloramentioning
confidence: 99%
“…Further, the neonatal gut microbiota is central to spleen development (19), and germ-free mice have defective spleen myeloid cells (20). The gut microbiota also modulates systemic and splenic inflammatory cells induced by sleep deprivation and lipopolysaccharide (LPS) administration (21,22). The spleen-gut axis is further supported by the disappearance of murine intestinal immunoglobulin A (IgA)-secreting plasma cells after splenectomy (23), but additional evidence is needed to better define this interaction.…”
Section: Introductionmentioning
confidence: 99%